Learning dynamics: A fundamental building block in social models. Comment on "Collective learning modeling based on the kinetic theory of active particles" by D. Burini et al. - Knopoff, Damián Alejandro (2016)
This paper comments the article by Burini et al. with special emphasis to the modeling of social systems, where learning is a key aspect to model their complex and evolutionary nature.